Microbial biocatalysis of quercetin-3-glucoside and isorhamnetin-3-glucoside in Salicornia herbacea and their contribution to improved anti-inflammatory activity. Issue 9 (3rd February 2020) - Ahn, Hyung Jin; You, Hyun Ju; Park, Myeong Soo; Li, Zhipeng; Choe, Deokyeong; Johnston, Tony Vaughn; Ku, Seockmo; Ji, Geun Eog
Abstract : Bifidobacterium animalis subsp. lactis AD011 catalyzed >85% of quercetin-3-glucoside and isorhamnetin-3-glucoside into quercetin (Q) and isorhamnetin (IR), respectively, in 2 h. These Q and IR showed improved anti-inflammatory activity. Abstract : Salicornia herbacea (glasswort) is a traditional Asian medicinal plant which exhibits multiple nutraceutical and pharmaceutical properties. Quercetin-3-glucoside and isorhamnetin-3-glucoside are the major flavonoid glycosides found in S. herbacea . Multiple researchers have shown that flavonoid glycosides can be structurally transformed into minor aglycone molecules, which play a significant role in exerting physiological responses in vivo . However, minor aglycone molecule levels in S. herbacea are very low. In this study, Bifidobacterium animalis subsp. lactis AD011, isolated from infant feces, catalyzed >85% of quercetin-3-glucoside and isorhamnetin-3-glucoside into quercetin and isorhamnetin, respectively, in 2 h, without breaking down flavonoid backbones. Functionality analysis demonstrated that the quercetin and isorhamnetin produced showed improved anti-inflammatory activity vs. the original source molecules against lipopolysaccharide induced RAW 264.7 macrophages. Our report highlights a novel protocol for rapid quercetin and isorhamnetin production from S. herbacea flavonoids and the applicability of quercetin and isorhamnetin as nutraceutical molecules with enhanced anti-inflammatory properties.